Forensic law casebook judicial reasoning and the application of forensic science in criminal cases - Nemeth, Charles P. 1951- (CRC Press, 2024)
"Forensic Law Casebook: Judicial Reasoning and the Application of Forensic Science in Criminal Cases fills the current void by reviewing actual case law and translating the practical application of science to the courtroom. Each chapter represents a unique forensic discipline, providing a short introduction to the subject matter, the relevant case law and court cases that pertain to that subject area, and posing a variety of questions and issues to the student. All cases provided contains a sufficient portion of the legal decision-and its implications to the evidence and analytical practices of that discipline-in order to then pose critical and analytical questions to the student, once they have fully read the case material and the decision, and considered its implications"-- Provided by publisher.